1997
DOI: 10.1016/s0020-7292(97)00157-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving blood availability in a district hospital, Bo, Sierra Leone

Abstract: Even in settings with irregular electrical supply, storage of small quantities of blood is possible. Ready availability of blood may contribute to improved quality of obstetric care and improved survival among patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…4 Each hospital recruits donors for its own patients and processes the blood for local transfusion. These hospitals often handle less than 1,000 units a year [5][6][7] and experience difficulties in standardization, quality assurance and in maintaining supplies of high quality reagents. Recruiting voluntary donors from the community is complex and expensive and depends on regular education programs, venesection teams, vehicles and cold storage.…”
Section: Organization Of Transfusion Services In Sub-saharan Africamentioning
confidence: 99%
“…4 Each hospital recruits donors for its own patients and processes the blood for local transfusion. These hospitals often handle less than 1,000 units a year [5][6][7] and experience difficulties in standardization, quality assurance and in maintaining supplies of high quality reagents. Recruiting voluntary donors from the community is complex and expensive and depends on regular education programs, venesection teams, vehicles and cold storage.…”
Section: Organization Of Transfusion Services In Sub-saharan Africamentioning
confidence: 99%
“…Few studies have reported on the quality and capacity of blood transfusion services in sub‐Saharan Africa [4, 19–21]. The World Health Organization (WHO) has called for day to day data collection from blood transfusion units to improve the transfusion services at the facility level and to ensure accurate national and regional data [4].…”
Section: Introductionmentioning
confidence: 99%
“…In traditional societies in sub‐Saharan Africa, blood may be associated with taboos [11]. Negative attitudes towards blood donation for transfusion are also recognized and these include anxieties concerning the risk of human immunodeficiency virus (HIV) infection [12–15]. Concerns have been expressed about blood sampling for research purposes in a coastal community in Kenya [16].…”
Section: Introductionmentioning
confidence: 99%